Altered cerebral vessel amplitude and oscillation frequencies in Alzheimer's disease compatible with impaired amyloid clearance: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Grimmer, Timo; Kotliar, Konstantin; Ortner, Marion; Conradi, Anna; Hacker, Patricia; Hauser, Christine; Günthner, Roman; Muggenthaler, Claudia; Förstl, Hans; Diehl‐Schmid, Janine; Schmaderer, Christoph
Abstract: Background: Retinal vessels are similar to cerebral vessels in their structure and function. Using a non‐invasive in‐vivo technique, we demonstrated previously that retinal vessel response to flicker is more emphasized and delayed in patients with dementia due to Alzheimer's disease (AD) compared to healthy controls (HC). Increasing evidence suggests that interstitial fluid of gray matter appears to flow outward via paravascular spaces which are located alongside cerebral vessels possibly being passively propulsed by vessels' pulsatility. Impaired pulsatility resulting in impaired clearance of molecules such as beta‐amyloid may in parts explain amyloid deposition in the brain. Moderate low pulsatility frequencies of around 0.1 Hz have been reported as the driving force for paravascular drainage in mice just recently. We aimed to elucidate whether retinal vessels' pulsatility in particular at low frequencies (0.05‐0.15 Hz) is changed in AD at the stage of dementia or mild cognitive impairment (MCI). Methods: Three groups of participants were examined by Dynamic Vessel Analyzer (IMEDOS Systems): 17 patients, 72.0 (62.0 – 79.0) y.o. [median (1 st quartile – 3 rd quartile)], with mild‐to‐moderate dementia due to probable AD ; 23 patients, 69.0 (61.0 – 71.0) y.o. with MCI due to AD, and 18 anamnestic healthy control subjects 66.5 (61.3 – 66.5) y.o. without cognitive impairment (HC). Results: Power spectra of the temporal arterial curves differed between the groups. Especially at moderate low frequencies around 0.1 Hz (0.05 – 0.15 Hz) ADD and most MCI arterial oscillations, characterized by the normalized area under the power spectrum, prevailed over HC oscillations. Within the heart frequency range of 0.8 – 0.9 Hz retinal arterial pulsations in MCI and AD groups were significantly more emphasized as in the HC group. Conclusions: In ADD and MCI power spectra of retinal arterial oscillations seem to shift from very low to moderate low frequencies. Interestingly, the latter frequencies correspond to those reported for lymphatic vessels in humans and those for paravascular drainage in mice. The emphasized retinal arterial pulsation at moderate low frequencies in ADD and MCI group would be compatible with the view of compensatory upregulation of paravascular drainage in AD and strengthen the amyloid clearance hypothesis.